Counselling Youth Who Are at Risk for Suicide: Working the Tensions - White, Jennifer; Fleming, Reg; Harrison, Jennifer (Canadian Journal of Counselling and Psychotherapy, 2022)
The purpose of this qualitative study was to examine how counsellors narrate their experiences of assessing and counselling youth who are at risk for suicide, the challenges and opportunities they face, and the conditions that support them in working in a relational, ethical, and useful way. Our analysis focused on how counsellors described their experiences working with youth who are at risk for suicide, the prevailing discourses and institutional requirements shaping their accounts of their practice, and some of the potential effects of these ways of thinking, talking, and relating. Our findings show some of the specific ways that counsellors “work the tensions” in their therapeutic encounters with youth who are at risk for suicide. This involves compliance and critique as well as artful reinterpretation. We hope to make a useful contribution to a growing body of practice-based evidence that recognizes the value of flexible, relational, and reflexive approaches to counselling youth who are at risk for suicide.